Influence of herbicides on the antifungal activity of some fungicides against Phytophthora blight of pigeonpea - and R.H. SINGH, BIRENDRA SINGH, S.N. CHATURVEDI (Indian Phytopathology, 2002)
Two pre-emergence herbicides, fluchloralin and pendimethalin incited significant reduction in the growth and complete inhibition of sporangia development of Phytophthora drechsleri f.sp. cajani at > 50Î¼l/1; being most inhibitory at 20deg C. The herbicides also modified the in vitro toxicity of the fungicides on the mycelial growth in nutrient agar. Both herbicides enhanced the toxicity of Apron 35WS [metalaxyl] and Ridomil MZ-72 [mancozeb + metalaxyl] to the growth of P. drechsleri f.sp. cajani but reduced the toxicity of captafol. Of 12 pesticidal combinations tested, a synergistic effect was observed in 10, and an antagonistic one in 2 combinations. The present study indicates that fluchloralin and pendimethalin can be safely mixed with these two fungicides.